2017
DOI: 10.1111/conl.12357
|View full text |Cite
|
Sign up to set email alerts
|

Are Brazil deforesters avoiding detection? Reply to Richards et al. 2016

Abstract: The paper "Are Brazil deforesters avoiding detection?" recently published in Conservation Letters by Richards et al. 2016 has critical shortcomings and conclusions based on biased and not very robust analyses. Here, we provide clarifications to some of the most critical points regarding the monitoring of land use changes in the Brazilian Amazon and related greenhouse emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Three publications reported the underestimation of forest area loss in the PRODES data and likely casual factors 15,17,36 . The larger estimate of evergreen forest loss from the MOD100 dataset accentuates the likelihood of underestimates in other existing data products, specifically PRODES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three publications reported the underestimation of forest area loss in the PRODES data and likely casual factors 15,17,36 . The larger estimate of evergreen forest loss from the MOD100 dataset accentuates the likelihood of underestimates in other existing data products, specifically PRODES.…”
Section: Discussionmentioning
confidence: 99%
“…The PRODES forest product had high omission errors of about 40% and 28% in 2000 and 2010, respectively ( Supplementary Table 3), which can be attributed, to a large degree, to the spatial extent of satellite images to identify forest and the fact that Landsat images have a number of pixels with no good-quality observations in 1 year ( Supplementary Fig 11). PRODES forest data has a minimum mapping unit of 6.25 ha, thus it would not account for forest loss in small patches 15,36 . Compared with GFW and MOD100, PRODES underestimated forest-loss area by 67-127%.…”
Section: Discussionmentioning
confidence: 99%
“…PRODES monitoring is since 2008 used to enforce the Plan for Preventing and Controlling Deforestation in the Amazon, and a notable difference between PRODES and GFC is that PRODES exclusively considers loss of primary forest. Unlike GFC, PRODES also uses a minimum mapping unit of 6.25 ha (although patches of >1 ha are later included if they subsequently combine to exceed 6.25 ha) [ 47 – 50 ]. Unpublished accuracy assessments of PRODES (based on reference data from a few scenes of higher resolution RapidEye and SPOT data) indicate an overall accuracy exceeding 90% [ 51 , 52 ].…”
Section: Methods and Datamentioning
confidence: 99%
“…Recent commentaries (M. M. C. Bustamante et al, 2017;Rajão, Moutinho, & Soares, 2017) found our methods "useful," but questioned our focus on PRODES and not Brazil's other government satellite forest monitoring systems. We focused on PRODES because of its unrivaled, but unwarranted salience.…”
Section: Introductionmentioning
confidence: 96%
“…With one exception 1 , those products which are used for enforcement monitor no greater a subset of Amazon forest than PRODES. This exception was not publicly known before Bustamante et al (2017) and thus might not have triggered (much) evasion. finer resolution monitoring has existed since 2005, but it was ambiguous in their comment when this information began being supplied to enforcement officials.…”
Section: Introductionmentioning
confidence: 99%